Chronic Ethanol Ingestion Increases Nitric Oxide Production in the Lung - Polikandriotis, John A. (2007)
PURPOSE: Chronic ethanol (EtOH) ingestion increases the incidence of the Acute Respiratory Distress Syndrome (ARDS). The mechanisms underlying EtOH-induced susceptibility to lung injury continue to be defined. This study examines the hypothesis that EtOH increases endothelial nitric oxide synthase (eNOS) expression and activity in the lungs of a rat model of chronic EtOH ingestion. METHODS: Male Sprague Dawley rats were fed liquid diets containing EtOH (36% of calories) or Maltose-dextrin as an isocaloric substitution for EtOH (Control) for 6 weeks. Selected animals were also treated with the angiotensin converting enzyme (ACE) inhibitor, lisinopril (3 mg/L in diet) for 6 weeks. At study completion, animals were sacrificed, and lung tissue was collected for assays of nitric oxide (NO) metabolism or pulmonary microvascular endothelial cells (MVEC) were isolated for analysis of NO release. RESULTS: Compared to the Control diet, chronic EtOH ingestion increased lung H(2)O(2) production, eNOS expression and activity, lung cGMP content and levels of protein nitration and oxidation. MVEC from animals with chronic EtOH ingestion released greater amounts of NO. EtOH-induced increases in lung H(2)O(2) production, eNOS expression and activity, cGMP content, protein nitration and oxidation, and MVEC NO production were all attenuated by treatment with lisinopril. CONCLUSIONS: Chronic EtOH ingestion stimulates ACE-dependent increases in NO production in the lung. These novel findings indicate that chronic EtOH ingestion increases reactive species production in the lung parenchyma and provide new insights into mechanisms by which EtOH causes phenotypic alterations in the lung and its response to inflammatory stimuli.